Finitude and death in Western society: a reflection focusing on health professionals - Raylane da Silva Machado; Larissa Alves de Araújo Lima; Grazielle Roberta Freitas da Silva; Claudete Ferreira de Souza Monteiro; Silvana Santiago Rocha (Cultura de los Cuidados, 2016)
Aim: to carry out a reflection on how the vision of finitude/death in Western society influences the performance of health professionals.